2012
DOI: 10.1152/jn.01137.2011
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of quinpirole inhibition of ventral tegmental area neurons is linked to the phosphatidylinositol system and is induced by agonists linked to Gq

Abstract: Putative dopaminergic (pDAergic) ventral tegmental area neurons play an important role in brain pathways related to addiction. Extended exposure of pDAergic neurons to moderate concentrations of dopamine (DA) results in a time-dependent decrease in sensitivity of pDAergic neurons to DA inhibition, a process called dopamine inhibition reversal (DIR). We have shown that DIR is mediated by phospholipase C and conventional protein kinase C through concurrent stimulation of D2 and D1-like receptors. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 98 publications
4
28
0
Order By: Relevance
“…The EC 50 values for the two effects of neurotensin were also different further supporting the argument that the two effects of neurotensin occur through separate mechanisms. The EC 50 value for inhibition of the D2R IPSC by neurotensin was ϳ4 nM, much lower than the EC 50 value for the neurotensin-induced current (ϳ200 nM), and lower doses of neurotensin (1-10 nM) have often been used previously to examine the effect of neurotensin on D2R signaling Nimitvilai et al 2012;Shi and Bunney 1990;Bunney 1991, 1992;Werkman et al 2000) while higher doses of neurotensin (1 nM to 5 M) have been used to examine the neurotensin-induced inward current in DA neurons Jiang et al 1994;Jomphe et al 2006;Shi and Bunney 1991;St-Gelais et al 2004;Werkman et al 2000). In addition, partially inhibiting the neurotensin current with SKF 96365 did not have any effect on the neurotensincaused inhibition of the D2R IPSC.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The EC 50 values for the two effects of neurotensin were also different further supporting the argument that the two effects of neurotensin occur through separate mechanisms. The EC 50 value for inhibition of the D2R IPSC by neurotensin was ϳ4 nM, much lower than the EC 50 value for the neurotensin-induced current (ϳ200 nM), and lower doses of neurotensin (1-10 nM) have often been used previously to examine the effect of neurotensin on D2R signaling Nimitvilai et al 2012;Shi and Bunney 1990;Bunney 1991, 1992;Werkman et al 2000) while higher doses of neurotensin (1 nM to 5 M) have been used to examine the neurotensin-induced inward current in DA neurons Jiang et al 1994;Jomphe et al 2006;Shi and Bunney 1991;St-Gelais et al 2004;Werkman et al 2000). In addition, partially inhibiting the neurotensin current with SKF 96365 did not have any effect on the neurotensincaused inhibition of the D2R IPSC.…”
Section: Discussionmentioning
confidence: 97%
“…Putative DA neurons were identified by their location relative to the medial terminal nucleus of the accessory optic tract, the presence of hyperpolarization-activated cation currents (H current), the presence of spontaneous pacemaker firing, and the sensitivity to DA (Johnson and North 1992). Although recent studies have raised questions on the utility of using these measures to identify VTA DA neurons (Margolis et al 2006), the characteristics described above have been widely used in electrophysiology studies to identify DA neurons within the VTA (Beckstead et al 2004;Nimitvilai et al 2012;Nimitvilai et al 2013;Perra et al 2011;Roseberry et al 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This DIR is mediated by concurrent stimulation of D2 and D1-like receptors, requires 10 to 40 minutes to develop, and persists for up to 90 minutes (Nimitvilai and Brodie, 2010). Activation of the D1/D5 receptor linked to phosphatidylinositide (PI) accumulation, but not those that cause adenylyl cyclase (AC) activation, produced a decrease in sensitivity of the D2 receptor to its agonist (Nimitvilai et al, 2012c). DIR also requires the activation of phospholipase C (PLC) and conventional protein kinase C (cPKC), without involvement of AC, cAMP, or protein kinase A (Nimitvilai et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…DIR also requires the activation of phospholipase C (PLC) and conventional protein kinase C (cPKC), without involvement of AC, cAMP, or protein kinase A (Nimitvilai et al, 2012a). Recently, we have demonstrated that some (e.g., 5-HT 2 and neurotensin) but not all (e.g., a 1 -adrenergic and group I metabotropic glutamate) Gq-coupled receptors that stimulate the PLC and PKC pathway can mediate the reversal of D2 agonist inhibition (Nimitvilai et al, 2012c). …”
Section: Introductionmentioning
confidence: 99%